The origin and spread of olive cultivation in the Mediterranean Basin: The fossil pollen evidence. (May 2019) - Langgut, Dafna; Cheddadi, Rachid; Carrión, Josѐ Sebastián; Cavanagh, Mark; Colombaroli, Daniele; Eastwood, Warren John; Greenberg, Raphael; Litt, Thomas; Mercuri, Anna Maria; Miebach, Andrea; Roberts, C Neil; Woldring, Henk; et al.
Olive ( Olea europaea L.) was one of the most important fruit trees in the ancient Mediterranean region and a founder species of horticulture in the Mediterranean Basin. Different views have been expressed regarding the geographical origins and timing of olive cultivation. Since genetic studies and macro-botanical remains point in different directions, we turn to another proxy – the palynological evidence. This study uses pollen records to shed new light on the history of olive cultivation and large-scale olive management. We employ a fossil pollen dataset composed of high-resolution pollen records obtained across the Mediterranean Basin covering most of the Holocene. Human activity is indicated when Olea pollen percentages rise fairly suddenly, are not accompanied by an increase of other Mediterranean sclerophyllous trees, and when the rise occurs in combination with consistent archaeological and archaeobotanical evidence. Based on these criteria, our results show that the southern Levant served as the locus of primary olive cultivation as early as ~6500 years BP (yBP), and that a later, early/mid 6th millennium BP cultivation process occurred in the Aegean (Crete) – whether as an independent large-scale management event or as a result of knowledge and/or seedling transfer from the southern Levant. Thus, the early management of olive trees corresponds to the establishment of the Mediterranean village economy and the completion of the 'secondary products revolution', rather than urbanization or state formation. From these two areas of origin, the southern Levant and the Aegean olive cultivation spread across the Mediterranean, with the beginning of olive horticulture in the northern Levant dated to ~4800 yBP. In Anatolia, large-scale olive horticulture was palynologically recorded by ~3200 yBP, in mainland Italy at ~3400 yBP, and in the Iberian Peninsula at mid/late 3rd millennium BP.